Outcome of Persistent Low-Grade Cervical Intraepithelial Neoplasia Treated With Loop Electrosurgical Excision Procedure. Issue 4 (October 2016) - Spinillo, Arsenio; Gardella, Barbara; Iacobone, Anna Daniela; Dominoni, Mattia; Cesari, Stefania; Alberizzi, Paola
Abstract : Objective: The aim of the study was to evaluate the outcome of persistent (≥2 years) low-grade cervical intraepithelial neoplasia (CIN 1) treated with loop electrosurgical excision procedure (LEEP). Materials and Methods: A study of 252 subjects with persistent biopsy-confirmed CIN 1 diagnosed after low-grade squamous intraepithelial lesions or atypical squamous lesions of undetermined significance on Papanicolaou test and treated with LEEP. Post-LEEP follow-up cytological, colposcopic, and molecular diagnostic examinations were scheduled at 6 months, 1 year, and yearly thereafter. Results: The 252 subjects enrolled had a total number of 1, 008 visits per colposcopies (median = 3, range = 1–7) during a median post-LEEP follow-up of 25 months (range = 12–121). The cumulative incidence of CIN 2+ at 2 years and at 3 years of follow-up was 2.3% (4/176) and 5.5% (7/128), respectively, or 1.7 cases (95% CI = 1–2.8) per 100 woman-years. Low-grade cervical lesions during post-LEEP follow-up were diagnosed in 70 subjects (27.8%) or 10 cases (95% CI = 7.9–12.6) per 100 woman-years. Overall, persistent and multiple high-risk HPV infections during follow-up were associated with increased rates of CIN persistence or progression. Conclusions: Women with persistent CIN 1 after atypical squamous lesions of undetermined significance/low-grade squamous intraepithelial lesion treated with LEEP had a low rate of progression to CIN 2+ but remained at a high risk of low-grade cervical abnormalities during follow-up. This information should be taken into account when deciding on the treatment strategy and counseling women with persistent CIN 1. Abstract : After a median follow-up of 25 months, women with persistent CIN 1 treated with LEEP had a low rate of progression to CIN 2+.